Antibacterial and antidiarrheal activity of Butea Monospermea bark extract against waterborne enterobacter Cloacae in rodents: In-vitro, Ex-vivo and In-Vivo evidences. (15th September 2019) - Sharma, Divya; Patel, Saraswati; Verma, Kanika; Gudlawar, Shiva; Chakraborty, Dipjyoti; Paliwal, Sarvesh; Dwivedi, Jaya; Sharma, Swapnil
Abstract: Ethnopharmacological relevance: Butea monosperma (Lam.) Taub. (family Leguminosae), popularly known as 'Palash' possess numerous medicinal properties since ancient times. According to the Wealth of India, stem bark of this plant exhibits various therapeutic properties like antimicrobial, astringent, styptic, aphrodisiac, and anti-inflammatory. Aim of the study: The purpose of the present study was to investigate antibacterial and antidiarrheal effect of B. monosperma bark against newly isolated gram negative pathogenic bacterial strain Enterobacter cloacae. Materials and methods: Aqueous extract of B. monosperma bark (BMAqE) was subjected to LC-MS/MS analysis for determination of bioactive components. Antibacterial study of BMAqE was assessed using bacterial growth kinetic study, fluorescence spectroscopy, outer and inner membrane permeability assay, dehydrogenase inhibitory assay and protein leakage assay followed by field emission scanning electron microscope (FE-SEM) study. Antidiarrheal activity was studied using castor oil induced diarrhea model in albino rats followed by histopathology studies of rat ileum. Results: LC-MS/MS analysis of BMAqE revealed presence of twenty-two different active phytoconstituents out of which most of the constituents belong to flavonoid and polyphenol family. BMAqE showed MIC and MBC (IC90 ) value of 5 and 200 μg/mL against targeted bacterial strain. BMAqE exhibited potent and dose dependent bactericidal effect via disruption of integrity of bacterial cell membrane, enzymatic degradation, leakage of intracellular protein and ruptured bacterial cell. In castor oil induced diarrhea model, BMAqE (200 mg/kg; orally) caused marked reduction (75.66%) in the frequency of defecation and mean weight of faeces (0.54 ± 0.04) when compared to control group (2.26 ± 0.25). Histopathology study revealed marked restoration of cellular architecture of rat ileum tissue. Four known flavonoids were isolated from BMAqE using column chromatography. In ex-vivo study, BMAqE (0.0002, 0.0004 and 0.0006 g/L) and isolated flavonoids i.e. rhamnetin, quercetin, kaempferol and catechin (0.5, 5 & 50 μm) produced a significant ( p < 0.001) change in EC50 and indicated competitive phenomena via rightward shift of acetylcholine CRC with pA2 of 3.78, 8.0, 7.1, 7.0 and 6.9 respectively. Conclusion: BMAqE exhibits impressive antibacterial and anti-diarrheal activity and can be effectively used to eradicate water borne diseases. Graphical abstract: Image 1